Eco-Friendly Bridging Material: Experimental Characterization of Eggshells as an Affordable Natural Waste Non-Damaging Lost Circulation Material to Reduce Drilling Fluid Cost in Reservoir Drill-In-Fluid System - Al Asy'ari, Muhammad Rizqi; Afifabyan, M Naufal; Karimah, Riska (Journal of Earth Energy Engineering, 2022)
Lost circulation nowadays became one of the major problems in many drilling operations worldwide. This problem is complicated for it can significantly cause non-productive time during drilling operations. This research aims to study an eggshells as a LCM and to provide further insight about the reliability and cost analysis of eggshells as a potential drilling fluid additive. Moreover, the research successfully identified the usage of an abundant natural waste, i.e. eggshells, as an environmentally friendly fluid additive. This research also investigated the technical feasibility of the eggshells and also its economics impact on drilling operations. In addition, it is found that the eggshells can also act as a non-damaging LCM for production zone that is more affordable as compared to other natural waste loss circulation material and current commercially chemical. Series of laboratory tests were conducted such as mud balance for the density test, rheological test using viscometer Fann Vg, filtration loss test with filter press, and also alkalinity (pH) test. An excellent result from filtration loss test i.e. decreased fluid losses and showed great improvement almost same as commercially CaCO3 result in the filter cake thickness. The research proves great potential of the utilization of eggshells as a multi-purpose additive in a drilling fluid. Economic analysis also suggests that it can possibly be implemented and to be further developed for a large-scale field operations. Finally, it is found that using eggshells as LCM can reduce the cost up to 72.2 % cheaper than commercial CaCO3. It is also safe for drilling in the production zone (pay-zone) because of its solubility on acid that it can disappear during the acidizing job. If this paper can be implemented on a wide-range scale it will be very beneficial to reduce other commercial additives usage without losing its reliability.